Towards sustainable neighbourhoods: implementing an integrated evaluation system - Francesca Abastante; Margherita Penza (Valori e Valutazioni)
The idea of sustainable development is not new; however, the scientific literature has revived and renewed interest in this topic, emphasizing the need for a holistic approach that considers the complex interaction between buildings, their surroundings and the urban ecosystem. In this context, various methods and tools have been developed to assess and improve urban sustainability. This paper focuses on Neighbourhood Sustainability Assessment Tools (NSATs) as comprehensive tools that embrace both qualitative and quantitative dimensions, in line with the current sustainability paradigm. Starting from the existing NSATs, the present research proposes an implemented tool able to guide the design of urban projects considering a broad sustainability perspective. In order to do that, this paper applies a multi-methodological framework involving the analysis of the most relevant European NSATs, the indepth study of academic literature, the study of specific Italian tools and the inclusion of questionnaires to propose an innovative assessment model. The paper concludes with an analysis of the strengths, limitations and future prospects of the proposed model.